City vs Energy consumptions: Community-led Energy Planning (CLEP) practices from the world - Guida, Carmen (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban Practices section aims at producing, analyzing and reporting data on recent and relevant policies in the urban domain. This contribution aims at delving into the Community-led Energy Planning (CLEP) practices and some application from the world. Energy communities are a growing trend in urban planning, as cities seek to reduce their reliance on fossil fuels and increase their energy resilience. This paper presents a focus on CLEP applications and their main advantages and challenges. This section of Review Notes examines the urban planning practices that have enabled the growth of community-led energy planning practices and the movements that promoted and enables such shift.